Understanding the impact of HLA molecular mismatch in solid organ transplantation: Are we there yet?. Issue 1 (18th November 2020) - Jackson, Annette M.; Pinelli, David F.
Abstract : Although quantification of HLA molecular mismatch holds significant potential to assess risk for allograft rejection, effective clinical implementation continues to face substantial hurdles. See the article from Davis et al. on page 322 .